FENOMENA PENYEBARAN HOAX DAN LITERASI BERMEDIA SOSIAL LEMBAGA MAHASISWA UNIVERSITAS MUSLIM INDONESIA - Majid, Abdul (Komodifikasi, 2019)
The rapid dissemination of information without regard to the ethics of reporting in online media mainly sourced from social media makes it difficult for readers to distinguish which information is true and which is falsified on Facebook, WhatsApp, Line, and other social media. The spread of hoaxes or cybercrime on social media is one of the nation's threats that needs attention with media literacy. This study uses a descriptive qualitative method of phenomenology approach through open interviews with informants from the management of student institutions and the Student Activities Unit of the Muslim University of Indonesia which is determined by purposive sampling. the results of the study show the phenomenon of the spread of hoax news at the student institute of the Muslim University of Makassar in Indonesia, starting with the number of news posts, information and images on social media, from personal accounts to groups that are not based on checking the truth of the news, so that the news becomes viral because of continual diarrhea. to other people. The phenomenon of hoaxes triggers the ability of students' media literacy to disseminate information that is responsive, careful in reading the news filtering, thinking about and researching the truth rather than being spread because the sensation of wanting to be considered a source of information is fast, up to date to fellow students through social media.